Elements of organisation of integrated maternity care and their associations with outcomes: a scoping review protocol - Soo Downe; Ank de Jonge; Pim P Valentijn; Suzanne Thompson; Hester Rippen; Corine J M Verhoeven; Jolanda Liebregts; Bahareh Goodarzi; Jan Jaap Erwich; George Burchell; Ronald Batenburg; Eline F de Vries; et al. (BMJ Open)
Introduction Integrated care is seen as an enabling strategy in organising healthcare to improve quality, finances, personnel and sustainability. Developments in the organisation of maternity care follow this trend. The way care is organised should support the general aims and outcomes of healthcare systems. Organisation itself consists of a variety of smaller ‘elements of organisation’. Various elements of organisation are implemented in different organisations and networks. We will examine which elements of integrated maternity care are associated with maternal and neonatal health outcomes, experiences of women and professionals, healthcare spending and care processes.Methods and analysis We will conduct this review using the JBI methodology for scoping reviews and the reporting guideline PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews). We will undertake a systematic search in the databases PubMed, Scopus, Cochrane and PsycINFO. A machine learning tool, ASReview, will be used to select relevant papers. These papers will be analysed and classified thematically using the framework of the Rainbow Model of Integrated Care (RMIC). The Population Concept Context framework for scoping reviews will be used in which ‘Population’ is defined as elements of the organisation of integrated maternity care, ‘Context’ as high-income countries and ‘Concepts’ as outcomes stated in the objective of this review. We will include papers from 2012 onwards, in Dutch or English language, which describe both ‘how the care is organised’ (elements) and ‘outcomes’.Ethics and dissemination Since this is a scoping review of previously published summary data, ethical approval for this study is not needed. Findings will be published in a peer-reviewed international journal, discussed in a webinar and presented at (inter)national conferences and meetings of professional associations.The findings of this scoping review will give insight into the nature and effectiveness of elements of integrated care and will generate hypotheses for further research.